Unveiling the Hybrid n-Si/PEDOT:PSS Interface - Jaeckle, Sara; Liebhaber, Martin; Niederhausen, Jens; Buechele, Matthias; Felix, Roberto; Wilks, Regan G.; Bär, Marcus; Lips, Klaus; Christiansen, Silke (ACS Applied Materials and Interfaces, 2016)
We investigated the buried interface between monocrystalline n-type silicon (n-Si) and the highly conductive polymer poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), which is successfully applied as a hole selective contact in hybrid solar cells. We show that a post-treatment of the polymer films by immersion in a suitable solvent reduces the layer thickness by removal of excess material. We prove that this post-treatment does not affect the functionality of the hybrid solar cells. Through the thin layer we are probing the chemical structure at the n-Si/PEDOT:PSS interface with synchrotron-based hard X-ray photoelectron spectroscopy (HAXPES). From the HAXPES data we conclude that the Si substrate of a freshly prepared hybrid solar cell is already oxidized immediately after preparation. Moreover, we show that even when storing the sample in inert gas such as, e.g., nitrogen the n-Si/SiOx/PEDOT:PSS interface continues to further oxidize. Thus, without further surface treatment, an unstable Si suboxide will always be present at the hybrid interface.
CRIS-Team Scopus Importer:2023-03-07
Keywords: conducting polymers; device stability; hard X-ray photoelectron spectroscopy; hybrid materials; inorganic/organic; interface; solar cells